Refractory Urinary Incontinence in Girls: The Role of the Bladder Neck - Chrzan, Rafal (Frontiers in Pediatrics, 2017)
Background Prevalence of lower urinary tract dysfunction (LUTD) in children is between 6 and 9% with urinary incontinence (UI) being one of the most common symptom. Various aspects of lower urinary tract symptoms (LUTS) Anatomical anomalies of the urinary tract as well as neurogenic underlying pathology can results in LUTS. Comorbidities and long-term consequences of the LUTD for the female patients as well as genetic issues are also briefly discussed. The role of the bladder neck Thanks to urodynamics, we have learnt a lot about the lower urinary tract function, but the role of the bladder neck in the pathophysiology of LUTS in children is not clear. Secondary bladder neck hypertrophy is a well-described pathology, but there is no standardized treatment for this phenomenon. Primary bladder neck dysfunction has already been defined by the International Children’s Continence Society. Refractory UI in girls Uniform diagnostic protocols are used in these girls with UI. Treatment consists of standard urotherapy, additional interventions, and pharmacotherapy in selected cases. Those with refractory UI require careful reassessment to look for the unrecognized disorders. Invasive urodynamics should be done in those patients. Ultrasound of the bladder neck region and the pelvic floor can be helpful, but its interpretation is very subjective. In a small group bladder neck insufficiency can be found and those might benefit from a surgical intervention. Future perspective Strict criteria of the bladder neck insufficiency in children must be defined. Early surgical intervention in girls with bladder neck insufficiency might reduce the long period of intensive conservative treatment.